Effect of educational intervention on risk factors of cardiovascular diseases among school teachers: a quasi-experimental study in a suburb of Kolkata, West Bengal, India - Anubrata Karmakar; Aritra Bhattacharyya; Bijit Biswas; Aparajita Dasgupta; Lina Bandyopadhyay; Bobby Paul (BMC, 2023)
Abstract Objective This prospective study aimed to evaluate the effects of a health education intervention on cardiovascular disease (CVD) risk factors among school teachers. Methods The study, conducted from August 2016 to May 2017, involved teachers from four schools in Baruipur, West Bengal, India. It was a multicentric, quasi-experimental study with an intervention group receiving tailored health education promoting lifestyle modifications, while the control group received no intervention. Baseline and endline assessments included behavioural and biological characteristics related to cardiovascular health and risk assessment. Data were analysed using JAMOVI. Results The intervention group showed significant improvements in physical activity levels [Cohen's d (Cd): 0.43, p = 0.006] and the consumption of fruits and vegetables (Cd: 1.00, p = < 0.001). Notably, there was a considerable reduction in the consumption of salt (Cd: -0.93, p = 0.039), oil (Cd: -0.98, p = < 0.001), fast food (Cd: -0.99, p = < 0.001), junk food (Cd: -0.99, p = < 0.001), and red meat (Cd: -1.00, p = < 0.001) among participants. However, there were no significant improvements in biological characteristics within the intervention group. In contrast, the control group exhibited no significant changes in behavioural and biological characteristics compared to baseline. The intervention group showed a minor non-significant reduction (3.0%) in their 10-year cardiovascular risk compared to baseline (Cd: -1.00, p = 0.50), while the control group had a negligible non-significant increase (0.7%) in their cardiovascular risk (Cd: 1.00, p = 1.00). Conclusion Health education intervention positively influenced behavioural characteristics, such as physical activity and dietary habits, among school teachers. However, no significant improvements were observed in biological characteristics or cardiovascular risk factors.